Adverse reactions following first three doses of the BNT162b2 mRNA COVID-19 vaccine: A prospective cohort study on relationships with individual characteristics and previous experience of adverse reactions - Ayako Konishi; Wakaba Fukushima; Tomoka Matsuura; Satoko Ohfuji; Tetsuo Kase; Kyoko Kondo; Kazuhiro Matsumoto; Asae Suita; Emiko Mukai; Ayane Kasamatsu; Yasutoshi Kido; Yu Nakagama; et al. (Human Vaccines & Immunotherapeutics)
A clear consensus on the factors contributing to adverse reactions following the mRNA COVID-19 vaccine has yet to be reached. Therefore, the present study investigated adverse reactions following the first three doses of the BNT162b2 mRNA COVID-19 vaccine and examined associated factors, including previous experience of adverse reactions. Two prospective cohort studies were integrated for this study, and 218 participants (79% female; median age 46.5 years) who had completed all three doses of BNT162b2 were included in the final analyses. Data were collected through self-administered electronic questionnaires. Local and systemic adverse reactions following vaccinations were classified with severity grading. Modified Poisson regression models were used to examine the association of adverse reactions. Local reactions were reported by 91–96% of participants, with moderate or severe local reactions in 27–43%. Systemic reactions were reported by 56–88% of participants, with moderate or severe systemic reactions in 19–56%. Participants with a history of moderate or severe local reactions were more likely to subsequently have moderate or severe local reactions (relative risk: 2.32 [95% confidence interval: 1.52–3.55] for the second dose, 1.89 [1.33–2.69] for the third dose), but not systemic reactions. Participants with a history of moderate or severe systemic reactions were more likely to subsequently have moderate or severe systemic reactions (1.31 [0.99–1.72] for the second dose, 2.18 [1.56–3.06] for the third dose), but not local reactions. These results may contribute to a more detailed understanding of mRNA COVID-19 vaccines and provide information for future vaccine development.